Active matrix type display apparatus - AOKI, YOSHIRO; OTA, MASUYUKI (2005)
The active matrix display device of the subject invention comprises display elements 110 and pixel circuit 120 for providing driving current to the display elements and having a plurality of pixels 100 disposed on a substrate in a matrix form, image signal circuit Xm arranged along the pixels, and image signal driver 200 which provides a level current to a pixel via a image signal circuit after providing a base current to an image signal circuit. Each pixel circuit comprises a pixel switch SST for controlling the selection or non-selection of the pixel, and memorizes a differential current between level current and base current upon selection of pixel, and output the memorized differential current as the driving current to the display element upon non-selection of pixel.